BANGTAN SEONYEONDAN (BTS) MUSIC VIDEO “IDOL” AS A REPRESENTATION OF KOREAN POP CULTURE - Hani Gustiya Ningsih; Indra Tjahyadi (JURNAL LITERASI, 2022)
This research aims to find out about Korean traditional culture that is becoming popular culture in Korea today in BTS "Idol" video music. This research is qualitative - descriptive by using Stuart Hall's representation theory with cultural studies approach. The method of data collection used is literary research. The results of this study are; (1) Horangi (tiger), considered a holy creature that brings good luck and as a symbol of courage and strength, (2) Hanbook, modified traditional Korean clothes to become modern, (3) Paljak-jiboong, Korean traditional pavilion still in use for house roof design, (4) 'eolssu', Pansori and ggwaeng-gwari, traditional arts and musical instruments that are combined with the flow of modern music in the current Kpop song, (5) the habit of Yangban, a mild cough that indicates its existence still applied until now.